Computed Tomography Assessment of Sarcopenic Myosteatosis for Predicting Overall Survival in Colorectal Carcinoma: Systematic Review. Issue 2 (March 2022) - Franco Valle, Kevin; Lubner, Meghan G.; Pickhardt, Perry J.
Abstract : Background: As the US population ages, cancer incidence and prevalence are projected to increase. In the last decade, there has been an increased interest in the opportunistic use of computed tomography (CT) scan data to predict cancer prognosis and inform treatment based on body composition measures, especially muscle measures for sarcopenia. Objective: This article aimed to perform a systematic review of current literature related to CT assessment of muscle attenuation values for myosteatosis in colorectal cancer (CRC) survival prediction. Results: Initial broad search of CT and CRC yielded 4234 results. A more focused search strategy narrowed this to 129 research papers, and 13 articles met the final inclusion criteria. Twelve of 13 studies found a statistically significant decrease in overall survival according to Hounsfield unit (HU)–based sarcopenia, with hazard ratios ranging from 1.36 to 2.94 (mean, 1.78). However, the specific criteria used to define myosteatosis by CT varied widely, with attenuation thresholds ranging from 22.5 to 47.3 HU, often further subdivided by sex and/or body mass index. Conclusions: Current evidence suggests that a strong association between CT-based muscle attenuation values for myosteatosis assessment correlates with overall survival in CRC. However, more research is needed to verify these findings and determine appropriate threshold values for more diverse patient populations. Because CRC patients are staged and followed by CT, the opportunity exists for routine objective myosteatosis assessment in the clinical setting.